Digital Learning Media Innovation in Social Studies Education at Madrasah: A Literature Review - Arista Dwi Saputri; Labib Muzaki Shobir; Risa Fitria; Zulfa Husnawati (Universitas Negeri Yogyakarta, 2025)
Social studies (IPS) instruction in madrasah, Indonesia's Islamic basic and secondary education institutions, carries a dual mandate: delivering the national social studies curriculum while embedding Islamic values within teaching and learning. Yet IPS is frequently perceived by students as memorization-heavy and unengaging, a challenge that innovative learning media may help address. This article presents a literature review examining how digital and media-based learning innovations, including animated video, interactive multimedia, e-booklets, and virtual reality, can be applied to strengthen IPS instruction within madrasah settings. Thirty peer-reviewed sources published between 2016 and 2025 were thematically analyzed and organized into four clusters: (1) evidence for video- and animation-based learning media, (2) media innovation specifically within IPS instruction, (3) pedagogical foundations including motivation, constructivism, and technological pedagogical content knowledge (TPACK), and (4) institutional and teacher-level support for technology integration. The review finds consistent evidence that well-designed digital media improves student motivation, activity, and learning outcomes across subjects and levels, and that comparable gains have been documented specifically within IPS classrooms. A case study of Kurikulum Merdeka implementation at a madrasah aliyah further indicates that social studies content can be taught in alignment with religious values without sacrificing curricular rigor. The review concludes that digital learning media innovation offers a practical, evidence-based pathway for madrasah to strengthen IPS instruction while preserving their distinctive religious-values mission, and it recommends further classroom-based research conducted directly within madrasah settings.